Evaluating the efficacy of commercial Bacillus thuringiensis israelensis FOR Aedes albopictus LARVAL control in various land use - Othman Wan-Norafikah,; Zaifol Atiqah-Izzah,; Chee, Dhang Chen; Mohd Sofian-Azirun,; Asri Lailatul-Nadhirah,; Mohammad Johari Ibahim1, (Penerbit Universiti Kebangsaan Malaysia, 2023)
A commercial bacterial product of Bacillus thuringiensis israelensis (Bti); Mosquito BTI from USA was tested for its efficacy in exterminating the local populations of Aedes albopictus larvae. Larval surveys were carried out to obtain field populations of Ae. albopictus from various land use namely dengue-risk and dengue-free housing localities as well as agrarian localities like oil palm plantations, rubber estates and paddy fields. A 24-hour larval bioassay using Mosquito BTI was performed on each Ae. albopictus population. Only a maximum of 2.00% mortality was observed by the end of the first four hours of exposure while a maximum of 25.00% mortality was displayed at 24 hours of exposure. Results showed the potential use of Bti in reducing local Ae. albopictus larval populations but more than 24 hours may be required to achieve complete mortalities among these populations upon exposure to Bti. Some limitations of this study were also discussed